Efficacy and safety of Kunxinning granules in patients with menopausal syndrome: a multicenter, randomized, double-blinded, and placebo-controlled trial - Zhou, Guirong; Chen, Danfei; Qian, Lin; Song, Dianrong; Zhang, Qin; Yan, Ying; Lin, Jie; Li, Li; Wan, Guiping; Li, Shuping; Hou, Lili; He, Yi; et al. (Frontiers in Pharmacology, 2025)
BackgroundMenopausal syndrome is a general term for a series of physical and psychological symptoms that women experience during menopause and perimenopause, which can lead to the occurrence of a variety of diseases. Many ingredients in Kunxinning granules have been used clinically to treat menopausal syndrome. However, evidence for its effectiveness is lacking.PurposeTo investigate the efficacy and safety of Kunxinning Granules in patients with menopausal syndrome and to fully verify its clinical application value. Study design: A multicenter, randomized, double-blinded, placebo-controlled trial.MethodsEligible participants from 9 hospitals were randomly assigned in a ratio of 3:1 to the experimental group (Kunxinning granules) and the placebo group (Kunxinning granules simulated agent) for 12 weeks. The primary efficacy outcome was the score reduction of the modified Kupperman index compared with the baseline. The secondary efficacy index is the disappearance rate of 13 single symptoms of the modified Kupperman index. The evaluation time points are baseline, 4 weeks, 8 weeks, 12 weeks and 4 weeks of drug withdrawal.ResultsA total of 475 patients (356 in experimental group and 119 in placebo groups) were included in the analysis. The modified Kupperman index of patients in the experimental group and placebo group were 28.81 ± 6.81 and 27.61 ± 7.38. The modified Kupperman index of the experimental group improved after 4 weeks of treatment (experimental group: 21.45 ± 6.29, placebo group: 23.79 ± 6.90, 97.5%CI: -3.68 to −0.99, p = 0.007) and 8 weeks (experimental group: 15.18 ± 5.82, placebo group: 20.93 ± 7.29, 97.5%CI: −7.05 to −4.45, p < 0.0001), 12 weeks (experimental group: 10.27 ± 5.44, placebo group: 19.70 ± 7.25, 97.5%CI: −10.68 to −8.19, p < 0.0001) and 4 weeks of drug withdrawal (experimental group: 10.27 ± 5.44, placebo group: 19.70 ± 7.25, 97.5%CI: −10.86 to −8.35, p < 0.0001) were significantly lower than placebo group. Moreover, the experimental group’s modified Kupperman index reduction from baseline was better than that of the placebo group at 4 weeks, 8 weeks, 12 weeks of treatment and 4 weeks of drug withdrawal (p < 0.0001). Moreover, the experimental group had a good improvement effect on all 13 symptoms of the modified Kupperman index after 12 weeks of treatment. There were no significant differences in adverse events between the two groups.ConclusionKunxinning granules are a promising treatment for menopausal syndrome which can effectively reduce patients’ hot flashes and sweating, insomnia, irritability and urinary symptoms and improve their quality of life.Clinical Trial Registrationhttp://www.chinadrugtrials.org.cn/clinicaltrials.searchlist.dhtml, identifier CTR20140289.